The Association of Gene Expression and Single Nucleotide Polymorphism (rs 6152 SNP) in Androgen Receptor Gene with Recurrent Spontaneous Abortion (RSA) in Iraqi Women (Medico Legal Update, 2021)
The proposal target was determining the gene expression and single nucleotide polymorphism of Androgenreceptor gene (rs6152 G>T) in blood sample of recurrent spontaneous abortion (RSA) Iraqi females. Fiftyfemales (n=50) with RSA consulted Al-Elwiya teaching hospital from February to June 2019 and apparentlyhealthy fertile control (n=50) were enrolled. DNA and RNA were extracted from leucocytes to detrimentthe SNP and gene expression which were carried out by (RT-q PCR). The results showed non -significantdifference (p>0.05) in the mean of threshold cycle(?Ct) of androgen receptor gene between female with RSAand control. Assessing the 2???Ct in female with RSA, non -significant decreased expression of folding inandrogen receptor m RNA compared with control. The genotypes and allele frequencies in the two groupsshowed significant decrease in the heterozygous (GA) and mutant (AA) genotype frequencies in female withRSA, the frequency of wild (GG) genotype is increased in female with RSA. In conclusion, expression ofandrogen receptor gene didn’t affect in female with RSA, the mutant genotype may play as protective SNPagainst RSA.